LIPID PROFILE OF MALE LOCAL RABBIT (Lepus sp.) THAT GIVEN COMMERCIAL FEED SUPPLEMENTED BY COD LIVER OIL - ERMAYANTI, NI GUSTI AYU MANIK; OKA, I GUSTI LANANG; MAHARDIKA, I GEDE; SUYADNYA, PUTU (Jurnal Biologi Udayana; Vol 22 No 1 (2018): JURNAL BIOLOGI UDAYANA, 2018)
ABSTRACT   Cod liver oil as a source PUFA (Polyunsaturated Fatty Acid) has very diverse and complex benefits, including for heart health. This study aimed to improve the lipid profile of male local rabbit which was fed commercial supplementation of cod liver oil. The experimental design used was Completely Randomized Design (RAL) with four feed treatments, ie commercial feed without supplementation of cod liver oil (P0) as control, commercial feed supplemented by cod liver oil 1.5% (P1), commercial feed supplemented by oil liver of 3% cod (P2) and commercial feed supplementation of cod liver oil 4.5% (P3).Each treatment consists of eight rabbits. The variables observed were total cholesterol, triglyceride, LDL, and HDL levels. The data obtained were analyzed with ANOVA and if significantly different were tested further with DMRT. The results showed that supplementation of cod liver oil with different levels in commercial feed showed significantly different results (P <0.05) on total cholesterol, triglyceride, LDL, and HDL levels of local rabbit. It can be concluded that supplementation of cod liver oil in commercial feed to the extent 4.5% capable repair the lipid profile of male local rabbit because it can decreased  total cholesterol levels, decrease triglycerides levels, decreased LDL levels, and increased HDL levels.